OSAFT Library: An Open-Source Python Library for Acoustofluidics - Fankhauser, Jonas; Goering, Christoph; Dual, Jürg (Frontiers in Physics, 2022)
In this article, we present the Open-Source AcoustoFluidics Theories (OSAFT) library (version 0.9.14), a Python library for acoustofluidics. The focus of the library is the classical problem of a particle suspended in a fluid and subjected to an incident acoustic wave. The Python code provides easy access to a number of theories describing acoustic scattering, acoustic streaming, and most importantly the acoustic radiation force exerted on the particle. At the time of submission of this article, six different theoretical models and various limiting cases thereof are available. All are treating the problem of a single, spherical particle in an infinite 3D-domain subjected to an incident plane standing or plane traveling wave. The implementations of further theories are currently under development. Our code is designed to be extensible. A library of fluid and solid material models facilitates the implementation of new theories. A unified application programming interface (API), which is used across all models, makes comparisons between different theories straightforward. Such comparisons can be made directly by the user or through the plotting capabilities of our library. The code is distributed through Python's standard software repository PyPi. Illustrative examples on the project's website serve as a starting point for learning the library's API. For a more in-depth understanding of the code, complete documentation of the codebase, directed at users as well as future collaborators, is available online. In an effort to make the library as extensive as possible, the authors of this article are looking for collaborators on the project.